Aflatoxin contamination in food crops in Kenya: a systematic review - Libamila, Hans L.; Wakhisi, Clevin A.; Wanjala, Allan K. (International Journal of Research in Medical Sciences, 2025)
Aflatoxins, a group of toxic secondary metabolites produced by Aspergillus flavus and A. parasiticus fungi species, is a sub-chronic and multifaceted agricultural productivity and public health problem in sub-Saharan Africa. The health impacts of aflatoxin exposure are severe and long-term. Characterization of aflatoxin forms is a valuable aspect of this challenge because different forms; aflatoxin B1, B2, G1, and G2 which vary in toxicity and occurrence according to environmental factors and processing conditions. This systematic review bridges the existing gaps by aggregating evidence of levels and extent of aflatoxin contamination of maize, wheat, sorghum, and groundnuts in Kenya from 2010 to 2025. This systematic review employs a narrative synthesis to analyze aflatoxin infestation of maize, wheat, sorghum, and groundnuts in Kenya based on the preferred reporting items for systematic reviews and meta-analyses (PRISMA 2020) standards. The search includes a number of electronic databases and grey literature sources. The four studies indicate that aflatoxin infestation of Kenyan maize remains a significant public health and food security concern, with infestation levels frequently being higher than the regulatory limit (10 µg/kg). The results quantify high infestation in the Rift Valley and Meru County, respectively, as well as associate extreme infestations in Eastern Kenya with associated health dangers like HCC. Regional disparities, driven by moisture, and problems such as broken kernels, insect damage, and excessive moisture levels continue to emerge as contamination drivers. These findings underscore the need for specific interventions to address the environmental and human-related causes of aflatoxin accumulation in maize.